Weight-loss intervention using implementation intentions and mental imagery: A randomised control trial study protocol - Hattar, A.; Hagger, Martin; Pal, Sebely (BioMed Central Ltd., 2015)
Background: Overweight and obesity are major health problems worldwide. This protocol describes the HEALTHI (Healthy Eating and Active LifesTyle Health Intervention) Program, a 12-week randomised-controlled weight-loss intervention that adopts two theory-based intervention techniques, mental imagery and implementation intentions, a behaviour-change technique based on planning that have been shown to be effective in promoting health-behaviour change in previous research. The effectiveness of goal-reminder text messages to augment intervention effects will also be tested. The trial will determine the effects of a brief, low cost, theory-based weight-loss intervention to improve dietary intake and physical activity behaviour and facilitate weight-loss in overweight and obese individuals. Methods/Design: Overweight or obese participants will be randomly allocated to one of three conditions: (1) a psycho-education plus an implementation intentions and mental imagery condition; (2) a psycho-education plus an implementation intentions and mental imagery condition with text messages; or (3) a psycho-education control condition. The intervention will be delivered via video presentation to increase the intervention's applicability in multiple contexts and keep costs low. We hypothesise that the intervention conditions will lead to statistically-significant changes in the primary and secondary outcome variables measured at 6 and 12 weeks post-intervention relative to the psycho-education control condition after controlling for baseline values. The primary outcome variable will be body weight and secondary outcome variables will be biomedical (body mass, body fat percentage, muscle mass, waist-hip circumference ratio, systolic and diastolic blood pressure, low-density lipoprotein, high-density lipoprotein, total cholesterol, triglycerides, blood glucose and insulin levels), psychological (quality of life, motivation, risk perception, outcome expectancy, intention, action self-efficacy, maintenance self-efficacy, goal setting and planning), and behavioural (self-reported diet intake, and physical activity involvement) measures. We also expect the intervention condition augmented with text messages to lead to statistically significant differences in the primary and secondary outcome variables at the follow up periods after controlling for baseline values. Discussion: The planned trial will test the effectiveness of the theory-based HEALTHI program intervention to reduce weight and salient psychological, biomedical, and behavioural outcomes in overweight and obese adults. The study has been designed to maximise applicability to real world settings and could be integrated into existing weight management practices.